From high entropy alloys to diluted multi-component alloys: Range of existence of a solid-solution. (5th August 2016) - Laurent-Brocq, Mathilde; Perrière, Loïc; Pirès, Rémy; Champion, Yannick
Abstract: In order to systematically compare high entropy alloys (HEA) and conventional diluted multi-component alloys and to observe the transition between both, 13 Crx Mnx Fex Cox Ni100 − 4x multi-component alloys, where x takes values between 2 and 25, were processed so as to reach the stable state and then characterized. A unique fcc solid-solution is formed for a wide range composition, spanning from 0 to 90 at.% of Cr, Mn, Fe and Co. When the sum of Cr, Fe, Mn and Co contents is larger than 90 at.%, the system demixes into two quaternary phases. The existing thermodynamics models are unable to predict the range of existence of the solid-solution for the studied alloys. No microstructural transition between HEA and conventional diluted alloys is observed. The maximization of configurational entropy appears to be neither a sufficient nor a necessary condition to form a HEA. Consequently a new definition for HEA is needed. Graphical abstract: Highlights: The range of existence of a solid-solution for the Crx Mnx Fex Cox Ni100-4x is large. No difference nor transition in the microstructure between HEA and diluted multi-component solid-solutions were observed. Maximizing the configurational entropy is neither sufficient nor necessary to form a multi-component solid-solution. A new definition of high entropy alloys is needed.